Missed Opportunities for Diagnosing HIV via Routine Screening in an Inner- City Primary Care Clinic - Abigail Hankin; Sara Turbow; Jennifer Spicer; Heather Freiman; Bijal Shah; Natasha Travis (Georgia Southern University, 2015)
Background: Although routine, opt-out HIV screening has been recommended for nearly a decade, clinical practice has not kept pace. Here, we examine missed opportunities for HIV screening among patients newly diagnosed with HIV via a routine non-targeted opt-out HIV screening program in a primary care clinic at an inner-city safety-net hospital. Methods: Select demographic and clinical data were analyzed for all persons with a new HIV diagnosis between July 9, 2013 and August 31, 2015. Retrospective reviews of medical records were performed to identify missed opportunities for HIV screening in the year prior to HIV diagnosis. Results: Among 6,582 patients tested for HIV as part of the screening program, 27 patients had a new HIV diagnosis (0.41%). In the year prior to diagnosis, 19 (70%) of these had contact with the healthcare system but were not tested for HIV. At the visit associated with the new HIV diagnosis, 70% of patients did not present with an indication for risk-based HIV screening or symptoms potentially associated with HIV-related infections. Conclusions: Despite CDC recommendations for routine, non-targeted, opt-out HIV screening in all healthcare settings, 70% of patients newly diagnosed with HIV via routine screening in a primary care clinic had contact with the healthcare system in the year prior to the new HIV diagnosis but were not tested for HIV. These findings highlight the importance of routine, nontargeted screening to identify patients with HIV as well as continued provider and patient education about the value of routine HIV screening.